Epigonism Vis A Vis Authentic Islam: Authority Claim And Novelty Production - Nizar, Muhammad (JURNAL PENELITIAN, 2022)
This study focuses on acute epigenetic phenomena still inherent in modern civilization today. Epigonism is also more severe in academic research results, which tend to experience repetition of research. This is marked by a sharp decline in interest in Islamic studies, which then tends to copy the classical legacy, considered a novelty in research. On the other hand, Epigonism and claims of Islamic authentication have not yet encountered a meeting point against the most valid claim of Islamic orthodoxy by blaming other groups who are not in line. Another phenomenon that is not inferior is also blaming each other for the results of research in each science discipline, one of which is the common ground for Covid-19. This study recommends that to achieve a complete understanding of Islam, one should harmonize textualism and contextualism to align with any civilization and culture. In addition, there must also be an appreciative attitude towards research results that are not in line with the disciplines that are the focus and dialogue between sciences, namely multidisciplinary research is more focused than monodisciplinary research, which tends to be repetitive even though the place and object under study changes.